Isolation and Characterization of Wilt-Causing Pathogens of Local Growing Pepper (Capsicum annuum L.) in Gurage Zone, Ethiopia - Temesgen Oljira; Sefawdin Berta (International Journal of Agronomy)
The yield of pepper (Capsicum annuum L.) is extremely threatened by different diseases in Ethiopia. The objective of the study was isolation of wilt-causing pathogens and susceptibility test of local growing pepper. Eighteen pepper farming fields were selected for disease assessment study. The samples of Mareko Fana, Dubi, and Mitmita local cultivar pepper’s pods, seeds, leaves, stems, and roots were collected, surface sterilized, and cultured on potato dextrose agar (PDA). Selective peptone pentachloronitrobenzene (PCNB) agar medium was used for fungus. Similarly, for bacteria isolation, nutrient agar (NA) was used. Morphological and biochemical tests revealed eleven fungal isolates of Fusarium oxysporum f. sp. that were isolated. The pathogenicity test confirmed nine of them were virulent to Mareko Fana, Dubi, and Mitmita local pepper. It is confirmed that Fusarium oxysporum f. sp. is the pathogen Fusarium oxysporum f. sp. capsici. Besides, Ralstonia solanacearum was identified as a bacterium pathogen causing complex pepper wilt disease. The highest mean PDI was registered in Remuga Keble (93.0%) and the lowest in Buyi Keble (58.3%). Similarly, the highest mean PSI was recorded in Buyi Keble (87.0%) and the lowest PSI (54.5%) was registered in Tawlla Keble. Among 60 seeds, Mareko local pepper inoculated by F. oxysporum f. sp. and R. solanacearum shows the highest susceptibility of 55 (91.0%) and 30 (50.0%), respectively. However, Mitmita local pepper was registered as the lowest susceptibility to both F. oxysporum f. sp. and R. solanacearum of 28.3% and 30.0%, respectively. Based on the finding, it can be concluded that pepper wilt was caused by a complex of fungus Fusarium oxysporum f. sp. capsici and bacteria Ralstonia solanacearum sp. in the study area. So, it is recommended that an integrated disease management approach should be implemented to manage the complex diseases of the site.